2021
DOI: 10.1016/j.molmet.2021.101269
|View full text |Cite
|
Sign up to set email alerts
|

Diminished ketone interconversion, hepatic TCA cycle flux, and glucose production in D-β-hydroxybutyrate dehydrogenase hepatocyte-deficient mice

Abstract: Objective Throughout the last decade, interest has intensified in intermittent fasting, ketogenic diets, and exogenous ketone therapies as prospective health-promoting, therapeutic, and performance-enhancing agents. However, the regulatory roles of ketogenesis and ketone metabolism on liver homeostasis remain unclear. Therefore, we sought to develop a better understanding of the metabolic consequences of hepatic ketone body metabolism by focusing on the redox-dependent interconversion of acetoacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Surprisingly, we observed about 1/3 of normal blood BHB concentrations under KD in the liver KO (Extended Fig. 10d , k) , suggesting a role for non-hepatic ketogenesis under the strong stimulus of KD in compensating for loss of hepatic BHB production 35,3941 . We confirmed efficacy of the knockout via RT-qPCR showing increased induction of Hmgcs2 with KD, emphasizing ketogenesis, but an insignificant change in Bdh1 , supporting the lack of AcAc to BHB conversion in livers of both male and female liver BDH1 KOs (Extended Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Surprisingly, we observed about 1/3 of normal blood BHB concentrations under KD in the liver KO (Extended Fig. 10d , k) , suggesting a role for non-hepatic ketogenesis under the strong stimulus of KD in compensating for loss of hepatic BHB production 35,3941 . We confirmed efficacy of the knockout via RT-qPCR showing increased induction of Hmgcs2 with KD, emphasizing ketogenesis, but an insignificant change in Bdh1 , supporting the lack of AcAc to BHB conversion in livers of both male and female liver BDH1 KOs (Extended Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Finally, to directly test if induced extra-hepatic ketogenesis meaningfully contributes to blood BHB concentrations under KD, we generated a liver-specific knockout (KO) mouse of Bdh1 (Albumin-Cre; Bdh1 fl/fl ) that should produce only AcAc, not BHB, from the liver 35 (Extended Fig. 10a) .…”
Section: Resultsmentioning
confidence: 99%
“…IF also confers a protective effect against oxidative stress and inflammation by activating antistress responses, including nuclear respiratory factor (Nrf )-1, Nrf-2 and mammalian target of rapamycin (mTOR) pathways [16,17]. Moreover, IF increases NAD + /NADH through altering cellular metabolic processes which leads to the Sirtuin proteins activation [18]. We have recently shown that, Sirt3, which is a member of the Sirtuin family and is primarily located in mitochondria in the cells, plays an essential role in regulating cellular apoptosis and autophagy after oxidative neuronal stress [19].…”
Section: Introductionmentioning
confidence: 99%
“…To quantify energy metabolites using methods described in 46,47 enabled with the optional "-q" option; 3bp sliding-window trimming from 3' end requiring minimum Q30. Quality control was completed by FastQC.…”
Section: Isotope Tracing Untargeted Metabolomicsmentioning
confidence: 99%